Features of Elastoplastic Deformation Powder Composites of the "Iron Cast" Type - Mamedov, A.T.; Huseynov, M.Ch.; Musurzaeva, B.B.; Jafarova, A.A. (Herald of Azerbaijan Engineering Academy, 2023)
The features of deformation of a powder system consisting of plastic (iron) and elastic (cast iron) particles are considered. To solve the problem of deformation of such a system, the model of continuum mechanics is taken as a basis, although after compaction of a powder medium, it consists of a matrix and pores, which is called a powder or porous medium. In this case, to apply the principle of continuum, the region of space is subdivided into small subregions corresponding to the size of the powder particles. The considered mathematical problem makes it possible to solve the technological problems of pressing the axis of symmetrical products with height transitions.